DETERMINANTS OF SUPPLY CHAIN PERFORMANCE: A STRATEGIC POINT OF VIEW. - S M Sohel Rana; Abdullah Osman; Azuddin bin Bahari; Mohammad Solaiman (International Journal of Supply Chain Management, 2015)
With the application of supply chain strategy, retailers can make a wise decision to increase supply chain performance. This study is one of the novelties in supply chain management research because it aimed at empirically analyzing the influence of supply chain strategies as the determinants of retail supply chain performance. For the purpose of the study, data were collected with a structured questionnaire from 115 mangers of some selected retail chain stores in Bangladesh. Collected data were analyzed using Partial Least Squares method with smart PLS software version 2.0M3. The present study has shown some meaningful findings regarding the determinants of retail supply chain performance. Firstly, it is found in the study that agile supply chain strategy is the most pivotal factor influencing retail supply chain performance. The lean strategy was also found to be a contributor to the retail supply chain performance while hybrid strategy was found to exhort very weak influence in increasing the performance of retail supply chain. The findings of this study can benefit the supply chain managers involved in retailing. From this study retail managers can know which strategy they should adopt to bring forth substantial advantage for the companies by maintaining their supply chain in a better way.